Pengaruh Terpaan Iklan Spaylater “Belinya Sekarang - Bayarnya Nanti” di Youtube terhadap Perilaku Konsumtif Mahasiswa di Surabaya - Azzahra, Fathoyya Vya; A, Syifa Syarifah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study is to see what influence exposure to Spaylater adverts "Buy Now - Pay Later" on Youtube has on the purchasing habits of students in Surabaya. This is an explanatory study, and the method employed is a quantitative approach. This study employed a purposive sample strategy using the following criteria to determine the population: 1) 19-24 years old; 2) Surabaya University students; 3) Have seen advertising on Youtube for "Shopee Paylater Later - Buy Now, Pay Later"; and 4) Actively utilize Shopee Paylater services and have had difficulty managing costs. In this study, 97 persons were sampled, and primary data was gathered through the distribution of questionnaires. Furthermore, the gathered data were evaluated using the SPSS test tool, which performed data analysis in the form of multiple linear regression analysis. The findings of this study reveal that advertisement exposure characteristics, such as frequency, length, and intensity, have a positive and substantial impact on the purchasing behavior of students in Surabaya. Keywords: Advertisement, Youtube, Advertisement Exposure, Consumptive Behavior.